Research on the Effect of Authenticity on Revisit Intention in Heritage Tourism - Zhou, Gefen; Chen, Wenkuan; Wu, Yuting (Frontiers in Psychology, 2022)
The authenticity of heritage tourism is an important factor for attracting tourists. Research has shown that authenticity is related to revisit intention. However, little attention has been paid to the impact of heritage tourism authenticity on revisit intention. Drawing on cognitive appraisal theory, we constructed a model of the mechanism underlying this relationship. Questionnaires were distributed at one world heritage site (the Dujiangyan irrigation system) in China, and data from 596 valid cases were collected. Using structural equation modeling, the results showed that authenticity, directly and indirectly, affects tourists' revisit intention via memorable tourism experiences and place attachment. The current paper enriches existing literature on the relationship between authenticity and revisit intention and provides a theoretical basis for promoting authenticity and revisit intention in heritage tourism.